Pengaruh Tingkat Suku Bunga dan Rasio Keuangan Terhadap Nilai Perusahaan - Aditya Saputera Pakaya; Lanto Mariatin Amali; Herlina Rasjid (Masyarakat Ekonomi Syariah Bogor, 2025)
This research aims to determine the effect of interest rates and financial ratios on company value. It is a case study on property and real estate sector companies listed on the Indonesia Stock Exchange for 2019-2022. The approach used in this research is quantitative with multiple linear regression analysis methods. The sampling technique used in this research is purposive sampling with a population of 9 companies and samples that meet the criteria amounting to 36 data from Property and Real Estate sector companies. The data collection technique in this research uses secondary data, namely financial reports published by property and real estate sector companies listed on the Indonesia Stock Exchange (IDX). The study results show that partially, Interest Rates do not affect Company Value, Profitability does not affect Company Value, and Activity does not affect Company Value. Meanwhile, simultaneously, Interest Rates, Profitability, and Activity do not affect Company Value.